The study of the students' perception toward the characteristics of lecturers at UiTM Melaka in improving the academic performance / Siti Rosnita Sakarji, Nurbarirah Ahmad and Zaini Hj. Sa'at - Sakarji, Siti Rosnita; Ahmad, Nurbarirah; Hj. Sa'at, Zaini (2012)
Learning is an ongoing progress through one's lifetime. The new global knowledge-based workplace today calls for a clear commitment among the educator to produce the best students. In response to today's challenging environment, academic qualifications have become a compulsory consideration for people to possess a good position in their career. The roles played by the educators would facilitate the dvelopment of physical, social and intellectual potential of students. The process of learning and achieving good performance among students are a direct result of the educator's contributions. Thus, the main purpose of this study is to study the students' perception toward the characteristics of lecturers at UiTM Malacca in improving the academic performance. In order to help UiTM to improve their student's performance, the study was conducted to To identify the lecturers' characteristics that aligns with the students' perception in improving the students' academic achievement and to determine the relationship between the lecturers' characteristics and students' academic achievement. With the intention of identifying the student's perception, this study also attempted to identify to identify the student's view _and perception of lecturers based on the effective teaching characteristics-teacher's knowledge, lecturers' conduct in class, lecturer's communication skills and lecturer's physical attributes. In addition, the study conducted was to identify the relationship between effective teaching style for students and their performance in learning. With regards to the objectives, a set of questionnaire was developed and distributed to 200 students at UiTM Malacca. This study was conducted with some limitations whereby the respondents of this study were limited to the respondents whore were studying at UiTM Malacca. Therefore, the population of this study was limited and the information was only obtained by distributing a questionnaire within a limited time frame. Descriptive statistics that described frequency. Percentage, mean and standard deviation as well as Pearson r correlation coefficient was used to reach the objective of the study. The results revealed that the majority of the students were agreed that they perceived the good lecturers must have adequate knowledge, expertise, attitude and personality. The result also revealed that the effectiveness of the roles played by the lectures playa high impact to the student's academic performance. As a conclusion, it was identified that there was a strong relationship between the lecturers' characteristics and students' academic achievement. Some recommendations were made with regards to the improvement of the educators to ensure that they would be able to produce higher quality teaching towards their students. To the end, the study also suggested for future study to minimize the limitations for the study such as expanding the numbers of respondents to other educational institutions and to cover the characteristics of the students that might hinder the success in implementation of effective teaching and learning process as well as in increasing the academic performance. For future study, it is hoped to cover multiple levels of people who were directly involved in the education system to ensure a broader perspective will be put together in the study, thus increasing the reliability of the findings.